Biosynthesis of conjugated linoleic acid: current status and future perspectives - Lu Lin; Mei-Li Sun; Kaifeng Wang; Jian Gao; Xiao-Jun Ji; Quanyu Zhao (Bioresources and Bioprocessing)
Abstract Conjugated linoleic acid (CLA) has received much attention for its beneficial physiological effects, particularly anticancer and metabolic control activity. However, traditional sources rely on extraction and chemical synthesis, both of which are not commercially viable. This article describes the research progress on sustainable alternative biosynthesis methods for the production of CLA, which is an attractive approach for commercial production because of its high stereoselectivity and convenient purification process. Here, we offer a comprehensive review of the current state and research progress in the biosynthesis of CLA, including production strains, biosynthesis mechanisms and improvements in the biosynthesis of CLA by genetic engineering. Finally, future research directions for improving the biosynthesis of CLA are defined in the light of recent advances, barriers and trends in this field.